2021
DOI: 10.17227/ted.num51-12536
|View full text |Cite
|
Sign up to set email alerts
|

Las competencias ambientales clave en las actividades docentes del profesorado de ciencias

Abstract: Nuestra sociedad actual se caracteriza por un estado de crisis civilizatoria, donde la pobreza, la inequidad y los conflictos conforman un sistema de problemáticas de las relaciones sociedad-naturaleza, que hacen que la formación ambiental se haga necesaria y urgente en nuestro sistema educativo. El desarrollo de capacidades y formación de competencias ambientales de los docentes, particularmente de ciencias, son determinantes para permitir que en las instituciones educativas los estudiantes tengan una formaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
2
0
7
Order By: Relevance
“…Furthermore, in order to increase their impact, these actions should appear in the initial stages (ECE and PE), with the aim of training an informed, critical citizenship capable of participating in decision making to face current challenges [28]. However, they should also be promoted in PTT, but from a reflective approach in their professional practice, within the framework of the specific environmental competence for teachers [47,48]. Despite this, the results reflect a predominance of actions associated with conceptual and procedural learning at all educational stages ("learning conceptual knowledge", "learning to search for information", or "discovering fundamental aspects of the environment").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in order to increase their impact, these actions should appear in the initial stages (ECE and PE), with the aim of training an informed, critical citizenship capable of participating in decision making to face current challenges [28]. However, they should also be promoted in PTT, but from a reflective approach in their professional practice, within the framework of the specific environmental competence for teachers [47,48]. Despite this, the results reflect a predominance of actions associated with conceptual and procedural learning at all educational stages ("learning conceptual knowledge", "learning to search for information", or "discovering fundamental aspects of the environment").…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above, and that systems thinking, critical literacy, and action competence are key elements in environmental justice education [23], it can be concluded that the main limitation identified when working on environmental education in ECE, PE, and PTT classrooms from an environmental justice perspective is its lack of integration. One possible explanation for this is the strong theoretical focus of publications on both environmental education and environmental justice [37], which has generated a gap between research and educational practice, due to the lack of a definition of the didactic component [47]. This is also reflected in the selection of the study sample, since, out of more than 700 articles, only 88 proposals with classroom intervention were found, and only 49 of them contain detailed information on their implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados del análisis de contenido realizado demuestran que las actividades ofertadas por el MITECO en la CM desatienden las necesidades que se vienen demandando para abordar el cambio de valores y conductas en EA (Mogensen y Mayer, 2009;Mora y Guerrero, 2022;Wiek et al, 2015). Así, las propuestas siguen centrándose en una formación disciplinar y las temáticas más trabajadas se relacionan con contenidos ecológicos y biológicos (biodiversidad, contaminación, etc.).…”
Section: Discusión Y Conclusionesunclassified
“…Además, llama la atención que estas actividades carezcan de evaluación y no se asocien a una demanda cognitiva concreta. Y que, en los pocos casos que contemplan evaluación se trate de un cuestionario de satisfacción, o bien se centre en cuestiones conceptuales disciplinares de Biología o Ecología, o en cuestiones actitudinales y moralizantes, situación que debería moderarse (Mogensen y Mayer, 2009;Mora y Guerrero, 2022). En este sentido, los diseños didácticos en su conjunto (temáticas, contenidos, actividades, secuencia, evaluación, etc.)…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation